Diagnostic Techniques and Artificial Intelligence for Multiple Sclerosis Identification - Asma Raisi; Mahsa Nasiri; Hajar Danesh (Majallah-i Dānishgāh-i ’Ulūm-i Pizishkī-i Īlām)
Introduction:  Multiple sclerosis is a chronic autoimmune disorder causing the degeneration of the myelin sheath, affecting nerve signal transmission. Symptoms include muscle weakness, visual disturbances, balance impairments, and incoordination. Early diagnosis is crucial for effective disease management and preventing irreversible neurological damage. This research was designed to explore diagnostic methods and introduces machine learning for automated data analysis and faster diagnosis. Materials & Methods: This study reviewed diagnostic methods for multiple sclerosis (MS), including electroencephalography (EEG), electromyography (EMG), clinical data, cerebrospinal fluid analysis, magnetic resonance imaging (MRI), and optical coherence tomography (OCT). Artificial intelligence (AI)-based approaches were also introduced to enable automated data analysis and expedite disease diagnosis. A novel platform-based method was proposed as an exclusive approach for automated detection through the integration of established diagnostic techniques. Results: Findings indicated that magnetic resonance imaging (MRI) demonstrates high accuracy in the diagnosis of multiple sclerosis. Based on the average performance of artificial intelligence-based methods across the primary diagnostic modalities, accuracies of 90%, 75%, 80%, 90%, and 95% were achieved for MRI, optical coherence tomography (OCT), electroencephalography (EEG), electromyography (EMG), and cerebrospinal fluid analysis, respectively. The proposed platform integrates these modalities to enhance both the speed and accuracy of disease detection. Conclusion: The utilization of advanced diagnostic techniques, coupled with the integration of multiple methodologies, markedly improves the early detection and therapeutic intervention of multiple sclerosis, thereby reducing the associated complications of the disease.